PHYSIOLOGICAL RESPONSES OF UPLAND RICE; WATER AND NITROGEN UPTAKES AND WATER USE EFFICIENCY UNDER WET AND PARTIAL DRYING SOIL CONDITIONS - Kitilu, Mganga Joshua Fimbo (International Journal of Research -GRANTHAALAYAH, 2021)
Rice is an important cereal and staple food crop in Tanzania, the rice production has not met the demand, mainly due to water shortage. Dissemination of New Rice for Africa (NERICA) has been in progress to improve production in upland rice ecosystem. A pot experiment was conducted in a split plot design at university farm to elucidate water uptake, water use efficiency and nitrogen uptakes for two NERICA cultivars (NERICA1 and 2) and two Japanese rice cultivars ( and ). Amount of transpired water was recorded every day until maturity. Nitrogen uptake at booting and maturity growth stage were compared between these cultivars. The results indicated that amount of water transpired was greater for NERICA cultivars in the period from booting to maturity, in particular, under the dry soil condition. All the cultivars showed similar slope of regression lines between amount of transpired water and dry matter production (Water use efficiency), Nitrogen concentration per unit weight was higher in NERICA rice than in Japanese rice during grain filling stage. These results indicate that NERICA’s rice cultivars have high productivity due to higher water and Nitrogen uptake during grain filling stage compared with the Japanese rice cultivars tested.